2016
DOI: 10.1118/1.4943953
|View full text |Cite
|
Sign up to set email alerts
|

IMRT QA: Selecting gamma criteria based on error detection sensitivity

Abstract: We have introduced the error curve method, an analysis technique which allows the quantitative determination of gamma criteria sensitivity to induced errors. The application of the error curve method using DMLC IMRT plans measured on the ArcCHECK® device demonstrated that large errors can potentially be missed in IMRT QA with commonly used gamma criteria (e.g., 3%/3 mm, threshold = 10%, 90% pixels passing). Additionally, increasing the dose threshold value can offer dramatic increases in error sensitivity. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 53 publications
2
53
0
Order By: Relevance
“…Although γ analysis is widely used in clinical practice, recent publications have raised concerns on whether it is capable of catching planning or machine errors [14, 19, 20]. It was demonstrated that even with intentional errors, the pass rate may still be higher than 90 % [14, 19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although γ analysis is widely used in clinical practice, recent publications have raised concerns on whether it is capable of catching planning or machine errors [14, 19, 20]. It was demonstrated that even with intentional errors, the pass rate may still be higher than 90 % [14, 19].…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that even with intentional errors, the pass rate may still be higher than 90 % [14, 19]. In this study, we simulated machine errors with varying magnitudes, and the sensitivity was investigated with γ gradient and ROC analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Gamma‐index analysis 20 was used to compare the measurements and calculations, by applying a criterion of 3% local pixel dose difference (LPDD)/2 mm distance‐to‐agreement (DTA) and a threshold of 30% of the maximum dose. This criterion was determined based on previous studies,21, 22, 23 and the threshold was set according to the dose constraints of the critical organs.…”
Section: Methodsmentioning
confidence: 99%
“…The plan is verified by comparing the “in air” recorded cumulative EPID image with a predicted one. Additional tools based upon diode arrays can be employed, but concerns surround the lack of tissue equivalence and sparse data sampling [1]. Recently, an EPID-based computational method for online 3D dose verification has been developed [2].…”
Section: Introductionmentioning
confidence: 99%
“…Gel dosimetry has become a tool for moderately accurate dosimetry in a tissue equivalent or anthropomorphic geometry, however the material-specific and readout errors [4] as well as long readout times [5] prevail. Diode array based systems are perhaps the industry standard for verification of individual plans but these have distinct limits on spatial resolution [1][6]. Transit dosimetry based upon reconstructing the dose inside a phantom portal can achieve images [7][8], but still require a simulation-based scatter correction for accuracy and/or other assumptions about the beam depth dose curve in the media.…”
Section: Introductionmentioning
confidence: 99%